Cost-benefit of outcome adjudication in nine randomised stroke trials. (October 2020) - Godolphin, Peter J; Bath, Philip M; Algra, Ale; Berge, Eivind; Chalmers, John; Eliasziw, Misha; Hankey, Graeme J; Hosomi, Naohisa; Ranta, Annamarei; Weimar, Christian; Woodhouse, Lisa J; Montgomery, Alan A
Background: Central adjudication of outcomes is common for randomised trials and should control for differential misclassification. However, few studies have estimated the cost of the adjudication process. Methods: We estimated the cost of adjudicating the primary outcome in nine randomised stroke trials (25, 436 participants). The costs included adjudicators' time, direct payments to adjudicators, and co-ordinating centre costs (e.g. uploading cranial scans and general set-up costs). The number of events corrected after adjudication was our measure of benefit. We calculated cost per corrected event for each trial and in total. Results: The primary outcome in all nine trials was either stroke or a composite that included stroke. In total, the adjudication process associated with this primary outcome cost in excess of £100, 000 for a third of the trials (3/9). Mean cost per event corrected by adjudication was £2295.10 (SD: £1482.42). Conclusions: Central adjudication is a time-consuming and potentially costly process. These costs need to be considered when designing a trial and should be evaluated alongside the potential benefits adjudication brings to determine whether they outweigh this expense.